Ответ:
[tex] \frac{5}{6} - \frac{1}{3} = \frac{5}{6} - \frac{2}{6} = \frac{3}{6} = \frac{1}{2} [/tex]
[tex] \frac{7}{12} - \frac{11}{20} = \frac{7 \times 5}{12 \times 5} - \frac{11 \times 3}{20 \times 3} = \frac{35}{60} - \frac{33}{60} = \frac{2}{60} = \frac{1}{3} [/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
[tex] \frac{5}{6} - \frac{1}{3} = \frac{5}{6} - \frac{2}{6} = \frac{3}{6} = \frac{1}{2} [/tex]
[tex] \frac{7}{12} - \frac{11}{20} = \frac{7 \times 5}{12 \times 5} - \frac{11 \times 3}{20 \times 3} = \frac{35}{60} - \frac{33}{60} = \frac{2}{60} = \frac{1}{3} [/tex]